The Effect of Individual and Organizational Characteristics on Work Motivation and Employee Performance - Dwi Zulkarnian; Mahlia Muis; Nuraeni Kadir (Magister Management, Hasanuddin University, 2022)
The success of a company can be achieved by the creation of optimal employee performance. This study aims to analyze the extent of the influence of individual characteristics and organizational characteristics in improving performance when work motivation is used as an intervening variable. This type of research is quantitative research. In analyzing data, the study applied path analysis assisted by SPPS software. The results found that individual characteristics and organizational characteristics have a significant positive effect on work motivation. When associated with employee performance, it is organizational characteristics indicate a significant effect, but it did not for individual characteristics. Work motivation shows a significant effect on employee performance. The findings also indicate that work motivation can mediate the relationship between individual characteristics and employee performance, but it did not occur for the relationship between organizational characteristics and employee performance.